Информатика: организация и управление - Кукин Вячеслав Иванович (Экономика, 1991)
Экземпляры: КХ (20101112) / Инвентарный номер: 988635 / Цена: 2.40 / Сис.шифр: 65.9(2) / Авт.знак: К 89 / ГРНТИ: 20 / ББК: 65.386.8